A predicting model of child‐bearing‐aged women' spontaneous abortion by co‐infections of TORCH and reproductive tract. (26th March 2022) - Zuo, Qun; Gao, Zhangquan; Cai, Li; Bai, Linlin; Pei, Yu; Liu, Mengchao; Xue, Hongmei; Xu, Juan; Wang, Shusong
Abstract: To develop a predicting model of child‐bearing‐aged women' spontaneous abortion (SA) by co‐infections of TORCH and reproductive tract, in order to provide a reference tool for accurately predicting the risk of SA and guide the early prevention, diagnosis and treatment of SA. A prospective cohort study was designed based on 218 958 child‐bearing‐aged women following up in Hebei province in China from 2010 to 2017. Multivariable logistic regression analysis was used to select candidate predictive variables. Fisher's discriminant analysis was performed to build a predictive model, and the validity of the model was evaluated. The incidence rate of SA was 2.4%. Multivariable logistic regression analysis showed that age (OR = 3.507), adverse pregnancy history (OR = 1.509), co‐infections status of Candida and HBsAg (OR Candida positive×HBsAg negative = 4.091, OR Candida negative×HBsAg positive = 3.327, and OR Candida positive×HBsAg positive = 13.762), and co‐infections status of HBsAg, Rubella (IgG) and CMV (IgG) (ORHBs‐Ag negative×Rubella (IgG) negative×CMV (IgG) positive = 1.789, ORHBs‐Ag positive×Rubella (IgG) positive×CMV (IgG) negative = 3.809, and ORHBsAg positive×Rubella (IgG) positive×CMV (IgG) positive = 11.919) were the independent predictors of SA. The total discriminant rate reached 91%, with 82% of the sensitivity and 91% of the specificity. The predicting model of child‐bearing‐aged women' SA by co‐infections status has a good performance. The co‐infection status of TORCH and reproductive tract are suggested to be considered in pre‐pregnancy physical examination.